2018
DOI: 10.1021/acsomega.7b01981
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Wound Healing Properties of Polyacrylonitrile-Moringa Extract Nanofibers

Abstract: A simple and cost-effective material composed of polyacrylonitrile nanofibers containing different concentrations of moringa (MR) leaf extracts was fabricated for antimicrobial properties and wound dressing. The fabricated materials were characterized by scanning electron microscopy, thermal gravimetric analysis, and Fourier transmission infrared spectroscopy. The antibacterial sensitivity of the developed polyacrylonitrile-moringa extract nanofibers was evaluated against Staphylococcus aureus and Escherichia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 55 publications
(96 reference statements)
1
44
0
1
Order By: Relevance
“…Data from the study showed that Moringa influenced the healing properties of the material. At days 1, 4 and 7 of the wound dressing experiment, the percentage wound closure of the rat was the highest for the nanofiber containing 0.5 g of Moringa leaf extract (35, 87 and 95%, respectively) compared to the positive control medical gauze (29,75 and 93%, respectively) [38].…”
Section: Medicinal Plant Extracts In Wound Healingmentioning
confidence: 97%
“…Data from the study showed that Moringa influenced the healing properties of the material. At days 1, 4 and 7 of the wound dressing experiment, the percentage wound closure of the rat was the highest for the nanofiber containing 0.5 g of Moringa leaf extract (35, 87 and 95%, respectively) compared to the positive control medical gauze (29,75 and 93%, respectively) [38].…”
Section: Medicinal Plant Extracts In Wound Healingmentioning
confidence: 97%
“…So, the PAN nanofibers containing 0.5 g of M . oleifera extract exhibited the best antimicrobial and healing activity (Fayemi et al, 2018).…”
Section: The Types Of Plant Compounds Used In Electrospinningmentioning
confidence: 99%
“…Therefore, with increasing the concentration of the M. oleifera leaf extract, the healing properties also increased. So, the PAN nanofibers containing 0.5 g of M. oleifera extract exhibited the best antimicrobial and healing activity(Fayemi et al, 2018).4.1.16 | MangosteenGarcinia mangostana L. (G. mangostana) known as the Queen of Fruits, is a tropical fruit found in Southeast Asia. The G. mangostana skin used as a therapeutic agent for the treatment of diarrhea, fever, the skin infections, and wounds is the main component of Xanthone that is the bioactive substance in the skin of G. mangostana.…”
mentioning
confidence: 99%
“…Blending PAN with cellulose acetate can be used to increase the absorption properties of activated carbon nanofi bres [52]. PAN/gelatine blends can be used for the promotion of cell growth ( Figure 2) [53][54][55].…”
Section: Electrospinnable Polymer Materials For Wound Dressing Applicmentioning
confidence: 99%